2019
DOI: 10.1038/s41467-018-07972-7
|View full text |Cite
|
Sign up to set email alerts
|

How lasing happens in CsPbBr3 perovskite nanowires

Abstract: Lead halide perovskites are emerging as an excellent material platform for optoelectronic processes. There have been extensive discussions on lasing, polariton formation, and nonlinear processes in this material system, but the underlying mechanism remains unknown. Here we probe lasing from CsPbBr3 perovskite nanowires with picosecond (ps) time resolution and show that lasing originates from stimulated emission of an electron-hole plasma. We observe an anomalous blue-shifting of the lasing gain profile with ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(213 citation statements)
references
References 41 publications
(55 reference statements)
8
203
2
Order By: Relevance
“…As shown in Figure 2F, similar rapid decay corresponding to the stimulated emission process of <30 ps was measured by TRPL for CsPbX 3 NWs under strong excitation, and the electronhole plasma mechanism was responsible for the stimulated emission [35]. More recently, Schlaus et al further reported that the CsPbBr 3 NW lasing originated from the stimulated emission of an electron-hole plasma by TRPL and transient reflectance [39]. They observed an anomalous blue-shifting of the lasing gain profile with time up to 25 ps and assigned this as a signature for lasing involving plasmon emission.…”
Section: Optical Gainsupporting
confidence: 72%
“…As shown in Figure 2F, similar rapid decay corresponding to the stimulated emission process of <30 ps was measured by TRPL for CsPbX 3 NWs under strong excitation, and the electronhole plasma mechanism was responsible for the stimulated emission [35]. More recently, Schlaus et al further reported that the CsPbBr 3 NW lasing originated from the stimulated emission of an electron-hole plasma by TRPL and transient reflectance [39]. They observed an anomalous blue-shifting of the lasing gain profile with time up to 25 ps and assigned this as a signature for lasing involving plasmon emission.…”
Section: Optical Gainsupporting
confidence: 72%
“…High power conversion efficiency (PCE) can be achieved due to the large absorption coefficient, broadband absorption spectrum, and long carrier lifetime in these inorganic perovskites. CsPbX 3 are not only efficient light‐harvesting materials, but also light‐emitting materials with extremely high fluorescence quantum yield, narrow emission bandwidth, low lasing threshold, and tunable bandgap, which make them strong contenders for high‐performance of light emitting diodes (LEDs), lasers, and photodetectors . CsPbX 3 are also proved to be excellent nonlinear optical absorbers with strong third order nonlinear susceptibility (≈10 −10 esu) and large two‐photon absorption (TPA) cross‐sections (≈10 5 GM), which are two orders of magnitude larger than those of traditional quantum dots .…”
Section: Introductionmentioning
confidence: 99%
“…However, very recently, the authors have reported their newest results on the lasing mechanisms and recognized that it was not actually polariton lasing in CsPbBr 3 perovskite NWs. From systematically investigations on the time‐domain lasing and many‐body interaction in CsPbBr 3 perovskite NWs, they have demonstrated that the lasing was neither due to excitons nor exciton–polaritons, but originated from the stimulated emission of n‐EHP coupled with plasmons . The authors proposed an n‐EHP model for plasmon‐coupled emission in these CsPbBr 3 NW lasers and further established that the lasing mode distribution inside the NW depended closely on the excitation density and time.…”
Section: Cw Lasing In Perovskite Nwsmentioning
confidence: 99%
“…Moreover, some researchers proposed that an electron–hole plasma (EHP) mechanism is responsible for the lasing in perovskites . Very recently, Zhu and co‐workers have demonstrated that the lasing in CsPbBr 3 perovskite NW lasers was due to stimulated emission from a nondegenerate electron–hole plasma (n‐EHP) coupled with plasmons rather than from excitons or exciton polaritons . A n‐EHP model was proposed for these NW lasers, and the criterion for population inversion is defined byμnormale + μnormalh>Ee,ck + Eh,vkωnormalpwhere µ e , µ h represent the chemical potentials of electron and hole, and E e,c , E h,v express the kinetic energies of electron and hole in valence and conduction bands, respectively; while ω p stands for the plasmon frequency, which may be approximated byωnormalp=nnormaleenormal2m*εeffεnormalowhere n e and m * are the number density and band mass of electrons in the conduction band, ε eff and ε o stand for the effective dielectric constant and vacuum permittivity, respectively.…”
Section: Introductionmentioning
confidence: 99%